ANALISIS PENENTUAN SETTING DISTANCE RELAY PENGHANTAR SUTT 150 KV GIS PESANGGARAN – GI PEMECUTAN KELOD - Kholid Hidayatullah; Rukmi Sari Hartati; I W Sukerayasa (Program Studi Teknik Elektro UNUD, 2019)
The addition of UGC cable (Under Ground Cable) and equipment rating’s change for the reconfiguration from Air Insulated Swichgear into Gas Insulated Switchgear at Pesanggaran substation. Therefore need to reset distance relay settings so that relays can work more selectively and reliably. Using manual and simulation calculations, the results obtained from distance relay reset GIS Pesanggaran - GI Pemecutan Kelod, with impedance value 1 = 2.055 ?, zone 2 = 5.73 ? and zone 3 = 11.01 ? with time delay at zone 1 = 0 seconds, zone 2 = 0.4 seconds and zone 3 = 1.6 seconds. This setting shows that the reload setting value can secure the line from the 3 phase short circuit fault obtained from the simulation results.